Negotiating Salafism and national ideology of Indonesia: A study on the curriculum of Salafi educational institutions - Basya, Muhammad Hilali; Zaman, Ali Noer; Fuad, Ai Fatimah Nur; Pratama, Daffa Tantra (Indonesian Journal of Islam and Muslim Societies, 2026)
Over the past two decades, the Salafi movement in Indonesia has been seen as controversial due to its involvement in religion-based intolerance, violence, and terrorism. There is doubt about the extent to which Salafi educational institutions can nurture their students to live in accordance with the modern Indonesian nation-state. This study aims to examine the curriculum in formal and non-formal Salafi education and analyze their compatibility with the national ideology, Pancasila. Data collection was conducted through in-depth interviews, observation, and a documentary study over approximately three months at three Salafi educational institutions in Jakarta, Tangerang Selatan, and Bogor. This article argues that even though most Salafi schools increasingly adjust to modernity and the Indonesian curriculum, they are a representation of their founders, who are Salafi ulama campaigning for their Salafi ideological vision. The Salafi vision, emphasizing the purification of faith, ritual, and social aspects, leads its students to accumulate cultural capital that creates tension with Indonesian ideology, particularly concerning gender equality, religious pluralism, multiculturalism, and freedom of thought and expression. Selama dua dekade terakhir, gerakan Salafi di Indonesia dipandang kontroversial karena keterlibatannya dalam intoleransi berbasis agama, kekerasan, dan terorisme. Terdapat keraguan tentang sejauh mana lembaga pendidikan Salafi dapat membina siswanya untuk hidup sesuai dengan negara-bangsa modern Indonesia. Studi ini bertujuan untuk meneliti kurikulum dalam pendidikan formal dan non-formal Salafi serta menganalisis kompatibilitasnya dengan ideologi nasional, yaitu Pancasila. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan studi dokumen selama sekitar tiga bulan di tiga lembaga pendidikan Salafi di Jakarta, Tangerang Selatan, dan Bogor. Dalam artikel ini, kami berpendapat bahwa meskipun sebagian besar sekolah Salafi semakin menyesuaikan diri dengan modernitas dan kurikulum nasional, mereka tetap merepresentasikan para pendirinya, yaitu ulama Salafi yang memperjuangkan visi ideologis Salafisme. Visi Salafi yang menekankan purifikasi akidah, ritual, dan aspek sosial menyebabkan para siswanya mengakumulasi modal budaya yang menciptakan ketegangan dengan ideologi nasional, khususnya terkait kesetaraan gender, pluralisme agama, multikulturalisme, serta kebebasan berpikir dan berekspresi.